The Relationship Of The Level Of Self-Awareness With The Quality Of Life In Diabetes Mellitus Patients In The Wonosari Health Center Area, Bondowoso District - Nur Intan Ayu Berliana; Sasmiyanto; Ginanjar Sasmito Adi (Penerbit Hellow Pustaka, 2024)
Diabetes mellitus is a chronic or chronic disease characterized by increased blood glucose levels because the body is unable to produce insulin. Self-awareness is a person's ability to recognize feelings, be able to control themselves, and have a strong belief in their strengths and weaknesses. One's self-awareness is needed to improve the quality of life. Quality of life is a person's thoughts regarding satisfaction or well-being from various aspects of physical, psychological, social and environmental health. The aim of this research is to determine the relationship between the level of self-awareness and the quality of life in diabetes mellitus sufferers in the Wonosari Health Center area, Bondowoso Regency. This research uses a correlational design with a cross sectional approach. The sampling technique used was Quota Sampling with a total sample of 86 respondents. The results of this research showed that 61 respondents (70.9%) had a high level of self-awareness and the majority of 47 respondents (54.7%) had a high quality of life. Based on the results of statistical tests using the Spearman Rank (Rho) test with α=0.05, a p value of 0.001 was obtained, and an r value of 0.703 means that there is a strong relationship between the level of self-awareness and the quality of life in diabetes mellitus sufferers in the Wonosari Health Center area, Bondowoso Regency. Diabetes mellitus sufferers in the Wonosari Community Health Center area are expected to be able to increase self-awareness in order to maintain a high quality of life through participation in regular PROLANIS activities held by the Wonosari Community Health Center. Diabetes mellitus sufferers are also expected to be consistent in controlling diabetes mellitus, including monitoring blood sugar levels and implementing a healthy lifestyle.